2018
DOI: 10.1002/ehf2.12353
|View full text |Cite
|
Sign up to set email alerts
|

The prognosis of mid‐range ejection fraction heart failure: a systematic review and meta‐analysis

Abstract: We detected a significant difference between HFrEF and HFmrEF regarding all-cause death, and non-cardiac death, while HFpEF differed significantly from HFmrEF regarding cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 36 publications
6
37
1
7
Order By: Relevance
“…These findings are in concordance with recently published large scale meta-analysis, highlighting the distinct prognostic role of mid-range LVEF group. 20,21 We were able to demonstrate that patients with impaired LVEF at baseline irrespective of initial clinical presentation (stable CAD or ACS) remain at increased risk of death compared to patients with either preserved or mid-range impaired LV function throughout 5 years. Most studies, of heart failure with depressed systolic function, report only a single LVEF measurement, generally obtained at baseline.…”
Section: Discussionmentioning
confidence: 82%
“…These findings are in concordance with recently published large scale meta-analysis, highlighting the distinct prognostic role of mid-range LVEF group. 20,21 We were able to demonstrate that patients with impaired LVEF at baseline irrespective of initial clinical presentation (stable CAD or ACS) remain at increased risk of death compared to patients with either preserved or mid-range impaired LV function throughout 5 years. Most studies, of heart failure with depressed systolic function, report only a single LVEF measurement, generally obtained at baseline.…”
Section: Discussionmentioning
confidence: 82%
“…The composite outcome of all-cause death or HF rehospitalization was not different among these distinct groups. 17,19 On the other hand, a meta-analysis demonstrated that HFmrEF had a lower rate of cardiac mortality than HFrEF. 20 This discrepancy might be due to the difference in patient characteristics and treatment in each cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] In the meta-analysis of Altaie et al, only a few outcomes differed between HF phenotypes: patients with HFmrEF had a lower rate of all-cause death than those with HFrEF, whereas patients in the HFpEF group had a higher rate of cardiac mortality than those in the HFmrEF group. [ 69 ] With regard to sudden cardiac death, Pascual-Figaz et al revealed a higher risk for HFmrEF than HFpEF patients (HR 2.73; 95% CI [1.07–6.98]; p=0.036). [ 70 ] Conversely, non-cardiac mortality was higher among patients with HFrEF than HFmrEF.…”
Section: Prognosismentioning
confidence: 99%